THE PROTECTION OF CHILDREN’S RIGHTS AND GENDER EQUALITY IN THE PERSPECTIVE OF INTERNATIONAL LAW - Ahmad Rusly Purba (Pusat Studi Gender dan Anak, 2026)
This research is motivated by the high vulnerability of children, especially girls, to discrimination, violence, and various forms of exploitation in both the physical world and digital spaces. The main objective of this study is to analyze how international legal instruments regulate children’s rights and gender equality, their implementation in Indonesia, as well as the challenges and efforts to realize effective protection. This study employs a normative legal research method using statutory and conceptual approaches. Primary, secondary, and tertiary legal materials were collected through library research and analyzed qualitatively. The findings demonstrate that international law provides a robust legal framework through principles such as non-discrimination and the best interests of the child. Although Indonesia has ratified key instruments like the Convention on the Rights of the Child (CRC) and CEDAW, and established national regulations such as the Child Protection Law and Marriage Law amendments, implementation in practice remains challenging. These challenges, which create gaps between legal norms and practice, include cultural factors, economic conditions, weak law enforcement, and the impact of digital technology. Consequently, stronger law enforcement, increased public awareness, and multi-sectoral cooperation are necessary to ensure effective protection of children’s rights and gender equality in Indonesia in accordance with international legal standards.